2004
DOI: 10.1118/1.1649531
|View full text |Cite
|
Sign up to set email alerts
|

Computerized characterization of breast masses on three‐dimensional ultrasound volumes

Abstract: We are developing computer vision techniques for the characterization of breast masses as malignant or benign on radiologic examinations. In this study, we investigated the computerized characterization of breast masses on three-dimensional (3-D) ultrasound (US) volumetric images. We developed 2-D and 3-D active contour models for automated segmentation of the mass volumes. The effect of the initialization method of the active contour on the robustness of the iterative segmentation method was studied by varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…We have developed an automated computer classifier for differentiation of malignant and benign breast masses on threedimensional (3D) US volumetric images (15). Thus, the purpose of our study was to retrospectively investigate the effect of using the computer classifier we developed on radiologists' sensitivity and specificity for discriminating malignant masses from benign masses on 3D volumetric US images, with histologic analysis serving as the reference standard.…”
Section: Advances In Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…We have developed an automated computer classifier for differentiation of malignant and benign breast masses on threedimensional (3D) US volumetric images (15). Thus, the purpose of our study was to retrospectively investigate the effect of using the computer classifier we developed on radiologists' sensitivity and specificity for discriminating malignant masses from benign masses on 3D volumetric US images, with histologic analysis serving as the reference standard.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…The first step of computerized analysis (15) involved extraction of the mass boundaries in the 3D volumetric data set (ie, mass segmentation). Automated segmentation of breast masses on US images is a difficult task because of image speckles, posterior shadowing, and variations of the gray level both within the mass and within the normal breast tissue.…”
Section: Computerized Classification Of Masses In Us Volumetric Data mentioning
confidence: 99%
“…Improper use of these methods can lead to significant biases in the estimated performance levels. We reviewed all research articles on the development and evaluation of CAD schemes that were published in Medical Physics [15][16][17][18][19][20][21] and IEEE Transactions on Medical Imaging [22][23][24] in 2004. We found that, among the 10 papers we reviewed, nine employed incorrect evaluation methods leading to increased bias and/or variance in the estimated performance levels [9].…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that the use of complementary and/or redundant texture features allows a more robust segmentation. Sahiner et al (2004) characterize breast masses on three-dimensional ultrasound images. They developed 2D and 3D active contour models for an automated segmentation.…”
Section: Choosing the Right Texture Featurementioning
confidence: 99%